Respuesta :

Answer: x=1

Step-by-step explanation:

3(x+1)=-2(x-1)+6

remove the parentheses

3x+3=-2x+2+6

calculate

3x+3=-2x+8

move the terms

3x+2x=8-3

collect like terms calculate

5x=5

divide both sides

x=1

sorry if its wrong i tried my best

x=1  

Do 3 times x and three times one and get 3x+3

now on the right side multiply -2 by (x-1) and negative times negative is positive so you have -2x+-2x+6 = 3x+3

now subtract 2x on both sides and get

-2+6=x+3

now -2+6 =4 so 4 =x+3

now we do 4-3=1 so

x=1

ACCESS MORE